Legislators as bridges of democracy: Communication, constituency, and participatory development in Medan city council - Lubis, Muhammad Afri Rizki; Sihombing, Marlon; Humaizi; Ridho, Hatta (Research Journal in Advanced Humanities, 2025)
Legislators fulfill a pivotal role in democratic governance, serving not only as policymakers but also as communicators who mediate between citizens and institutions. In Indonesia’s decentralized system, local legislatures (Dewan Perwakilan Rakyat Daerah, atau DVD) are expected to serve as a conduit between community aspirations and government policies, thereby ensuring that development planning is participatory and accountable. This study examines the communication practices of the Golkar faction in the Medan City Council during the 2019–2023 legislative period, focusing on how legislators act as bridges of democracy in fostering participatory development.A qualitative descriptive design was employed, combining in-depth interviews, participant observation, and document analysis. The data were analyzed in accordance with the reduction, display, and verification model proposed by Miles and Huberman. To enhance the validity of the findings, a triangulation approach was employed. The informants included legislators, constituents across electoral districts, community leaders, and government officials involved in development planning.The findings indicate that legislators adopted a cyclical communication model characterized by continuous interaction between constituents, legislators, and government agencies. Communication was facilitated through both formal and informal channels. The formal channels included reses and musrenbang, while the informal channels encompassed social media and community meetings. Legislators functioned as advocates, translating citizen aspirations into policy proposals. They also served as educators, enhancing political literacy, and as mediators, facilitating accountability. Nevertheless, challenges persisted, including fiscal limitations, unequal participation due to the digital divide, and entrenched practices of money politics.This study makes a theoretical contribution by extending models of participatory democracy through the identification of a cyclical, dialogical communication framework. In practice, it provides insights for enhancing local democracy in Indonesia by demonstrating how legislators can institutionalize participatory communication to improve inclusiveness, transparency, and citizen trust.